UNESP Program of Youth and Adults Education - PEJA/Marília: articulation in the theory and the pratice on the formation's teacher and the perspective of social and communitary integration. - José Carlos Miguel (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
This paper aims to give evidence to one of the possibilities of bringing formation to the professionals that work with EJA (Youth and Adult Education), that is, the continuous formation, that follows the trajectory of the educator's work with his/her students, having as a support its insertion in search projects, in the perspective of a group process that involves action-reflection-action. It also aims to discuss the bases on which may be constructed mathematical and reading/writing concepts. Parting of the reality diagnostic to documental analysis to situate the EJA in the present Brazilian context debate the didactic and pedagogical action and finish to need of the epistemological curious teacher.